A total systems study of Company NGC an LPG refilling and distribution company - Collado, Angelo Immanuel G.; Del Rosario, Francisco Luis A.; Ednalino, Kenneth Anthony G.; Macabanti, Jerome A.
Northern Gas Corporation (NGC) is a liquefied petroleum gasoline (LPG) refilling and distributing company established in 1964. A family-owned business, NGC started by pioneering the promotion of using LPG as a household cooking fuel. It expanded its services to delivering LPG to commercial and industrial establishments in the .early 1980's, which greatly increased its profits. Over the years, the company has partnered with well-known brands of LPG as their distributors and refillers such as Mobil, Caltex, Liquigaz, and Petron. Currently, it is the distributor of the brand Fiesta Gas, owned by Petron Corporation. NGC operations include hauling of LPG from the refinery in Bulacan, refilling of 2.7kg, 5kg, 11 kg, 22kg, and 50kg LPG cylinders, installation of gas lines and equipment for new customer accounts, delivery of LPG, in cylinders and bulk. Out of the company's range of refilling services, refilling LPG cylinders for dealers has the annual largest production volume, but majority of the source of annual profit comes from refilling LPG, in 50-kg cylinders or in bulk orders, for commercial and industrial accounts. Being a 50-year old company, NGC takes pride in being one of the pioneers in the LPG industry, and with its long experience in the industry, have established itself as one of the most reliable companies to its customers. The company values quality customer service and follows strict safety regulations for its customers and employees. Furthermore, its strategic location in Metro Manila, being near to its serving customer accounts and its supply source, gives NGC another competitive advantage. However, in recent years, the company has been struggling to be competitive in the industry. Since the pullout of its biggest business partner, Liquigaz, in 2012, refilling and delivery operations have decreased and have not been able to garner volume demand from the market. In addition, the only sales manager that works in acquiring customer accounts since the early beginnings of the company has retired, with minimal documentation to help in the transition to a new sales person. Since the company only recently started hiring new sales executives to do the sales workload, the success of the new hires has been dismal. Out of the 8 total sales executive hires since 2013, only 1 was able to stay and deliver new sales volumes, and none of the past hires delivered any new sales volumes. The only current hire was only able to garner a total of 3,611 kg new sales volume in three months of work, or 1,204kg per month in 2015. Since the decline of sales volume demand, the plant refilling operations output has also decreased. Through a conducted work sampling and time study in the bulk refilling plant of NGC, where all the refilling of LPG cylinders occur, the percent non-productive of the plant and its assigned refillers has been about 73% and 40% respectively. In addition, the plant's capacity is not maximized operationally, with a utilization rate of only 33% for the refilling plant and 37% for bulk order operations. Analyzing the company's FY 2014 income statement reports and making some assumptions on LPG selling prices and cost of goods sold verifies that the company is currently struggling to be competitive in the industry since 2013. The LPG industry states that the minimum annual profit margin required for LPG refilling companies to be competitive is 20%. However, the annual profit margin reported by the company has been below the 20% mark since 2013. In FY 2014, the profit margin was only about 13% based on the financial reports. The major reason for this is the decline of annual sales volume with a negative growth rate of 4.3% from 2009 to 2014. This also translates to a net revenue loss of about Php21.6 million. Through a total systems study of NGC, the group was able to create and evaluate alternative solutions in order to address this problem. The objective of this evaluation is to increase NGC's profit margin by 7% in a period of 5 years. Majority of these alternatives focused on increasing sales capacity by reviewing and revising the procedures in sales operations documentation and sales hiring process, have more sales executives acquiring more customer accounts, and increasing motivation of the sales group to reach target sales. Furthermore, a five-stage market study was recommended with the goals of identifying major competitors and market share, understanding end-user motivation, and developing dealer relations. The knowledge obtained from this proposed marketing analysis would empower the company to formulate more strategic decisions with regards to promoting their particular brand of LPG. Alternatives in optimizing operational expenses were also considered with the objectives of decreasing non-productive costs. One alternative is limiting the working hours of casual or contractual workers. Through a rough forecast and simulation of implementing the sales alternatives, the study showed a yearly increase in sales volume and profit margin, with the number of sales executives as a variable, but reaching 20% profit margin cannot be reached within 5 years. With the increase of sales demand, the possible problem may arise when the current plant capacity cannot meet the increase in volume output demand. Thus, alternative ways of improving plant capacity were also considered, such as investing in upgrades in the aging refilling equipment, and adding trolleys and ramps for proper material handling of workers. The study recommends that NGC focus on improving its sales operations because this is the immediate need of the company at the moment to reverse the decline trend of sales volume and revenue. The most immediate solution is to revise its sales hiring process and proper documentation of sales operations in order to produce more promising results in hiring new sales executives and to effectively increase their selling capacity. Also, a market study may prove beneficial in the long run as it would provide information for the company to move forward as a more competitive one. Once the company sustains an annual growth of sales volume, this will be when the company reviews its strategic alternatives in upgrading the plant capacity to meet growing customer demand.